Visual immersive geometry - Liu, Zeyan (2017)
This project studied BS SDK and discovered a way to run FVRML (Functional-based extension of Virtual Reality Modeling Language) on the latest version of Mozilla Firefox browser (50.1.0) as well as the latest version of IE browser (Internet Explorer 11)